Using the “mind map” method in the development of students’ vocabulary in English - Meirbekov, A.K.; Abzhekenova, B.G. (KU Publ., 2022)
This article is devoted to the “mind map” method of developing the vocabulary of students in English. In the process of learning a language, the main principle before developing language skills is the development of vocabulary since insufficient vocabulary limits the capabilities of students. It also reduces the student’s activity and interest during the lesson. Improving the quality of education requires the development of a work plan in accordance with the level of education, the interests and values of students, taking into account each level. It is also important to use effective methods to improve the quality of students’ knowledge. Thus, this article aims to learn vocabulary easily using the “mind map” and to make it possible to reuse previously used words using the “mind map”. During the study, a review of the literature on this topic was conducted. As a result, vocabulary development through the “mind map” is presented as a method for improving the effectiveness of the educational process.
Ағылшын тілінен оқушылардың сөздік қорын дамытуда «mind map» әдісін қолдану
Использование метод «mind map» в развитии словарного запаса учащихся на английском языке
Keywords: vocabulary; English; teaching; mind map; development; language; method; efficiency; skills